A mixed-methods case study examining the developmental networks of athletes in a wheelchair rugby team. (September 2021) - Lefebvre, Jordan S.; Alexander, Danielle; Sweet, Shane N.; Bloom, Gordon A.
Abstract: Objective: The purpose of this study was to examine the developmental networks of athletes in a wheelchair rugby team. Design: A convergent mixed-methods design embedded within an instrumental case study (i.e., wheelchair rugby team). Methods: Participants included seven wheelchair rugby athletes (five male; two female) and seven non-athletes linked to the team (four male; three female). Five athletes had a spinal cord injury and two athletes had a congenital impairment. Non-athletes included one current coach/romantic partner, three parents, one kinesiologist, and two administrators. The quantitative data were analyzed using social network analysis. The qualitative data were analyzed using thematic analysis. Results: Wheelchair rugby athletes had small networks ( M = 6) that included a diversified set of developmental relationships, such as peers, coaches, parents, romantic partners, and rehabilitation specialists. Furthermore, the quality of relationships varied as a function of the type of developmental relationships, which led to distinct developmental contributions, such as athlete's integration into the wheelchair rugby community, continued participation in this sport, and athletic development. Conclusion: These results provide pertinent and useful information on the relationships of para sport athletes, including the development of collaborative learning environments for them. Highlights: Developmental networks help understand someone's personal relationships. Athletes had a small but diverse developmental network. Networks included peers, coaches, partners, family, and rehabilitation specialists. Peers provided the greatest developmental contribution to athletic development.